Optimisation of Image Interpretability and Geometric Accuracy of Airborne Videography - Irawan Sumarto (Journal of Mathematical and Fundamental Sciences, 1998)
Airborne video images which have several advantages over satellite images and aerial photographs were captured over some selected areas. After they were refined to increase their interpretability, the images were assessed in accordance with the existing map accuracy specifications. Four algorithms of image refinement were tested. These include projective, row duplication, row interpolation and statistical correlation function. Numerous test points were selected on the image and their coordinates were compared to their ground positions. The results suggest that a solid-state video camera can provide images that are sufficiently accurate for medium-scale topographic mapping.Ketelitian Geometrik dan Optimalisasi Tingkat Ketajaman Citra VideoCitra video, yang mempunyai beberapa keuntungan dibandingkan dengan citra satelit dan foto udara, diperoleh dari hasil penerbangan di atas suatu daerah. Setelah citra tersebut direstorasi untuk meningkatkan tingkat ketajamannya, dilakukan proses fotogrametri untuk mengevaluasi tingkat ketelitian geometriknya. Restorasi citra dilakukan secara digital dengan empat macam teknik, yaitu projektif, interpolasi baris, duplikasi baris, dan kolerasi statistic. Evaluasi keteletian geometrik dilakukan dengan membandingkan koordinat sejumlah titik yang diamati pada citra video dengan posisi seharusnya di lapangan. Hasil pengujian mengindikasikan bahwa kamera video dapat digunakan pada pemotretan udara bagi keperluan pemetaan topografi skala menengah.